Characterization and use in wheat breeding of leaf rust resistance genes from durable varieties - Dieguez, Maria Jose; Lopez, Micaela; Altieri, Emiliano; Pergolesi, María Fernanda; Dabove, Marisol Alicia; Cuyeu, Alba Romina; Justus, Nadia Alejandra; Kandus, Mariana Virginia; Ingala, Lorena Romina; Sacco, Francisco (MDPI, 2023)
Leaf rust is one of the most significant diseases of wheat worldwide. In Argentina, it is one of the main reasons for variety replacement that becomes susceptible after large-scale use. Some varieties showed durable resistance to this disease, including Buck Manantial and Sinvalocho MA. RILs (Recombinant Inbred Lines) were developed for each of these varieties and used in genetics studies to identify components of resistance, both in greenhouse inoculations using leaf rust races, and in field evaluations under natural population infections. In Buck Manantial, the APR gene LrBMP1 was associated with resistance in field tests. In crosses involving Sinvalocho MA, four genes were previously identified and associated with resistance in field testing: APR (Adult Plant Resistance) gene LrSV1, the APR genetic system LrSV2 + LrcSV2 and the ASR (All Stage Resistance) gene LrG6. Using backcrosses, LrBMP1 was introgressed in four commercial susceptible varieties and LrSV1, LrSV2 + LrcSV2 and LrG6 were simultaneously introgressed in three susceptible commercial varieties. The use of molecular markers for recurrent parent background selection allowed us to select resistant lines with more than 80% similarity to commercial varieties. Additionally, progress towards positional cloning of the genetic system LrSV2 + LrcSV2 for leaf rust APR is reported.